Dexamphetamine effects on prepulse inhibition (PPI) and startle in healthy volunteers - Chitty, K.; Albrecht, Matthew; Graham, K.; Kerr, C.; Lee, J.; Iyyalol, R.; Martin-Iverson, M. (Springer, 2014)
Rationale: Amphetamine challenge in rodent prepulse inhibition (PPI) studies has been used to model potential dopamine involvement in effects that may be relevant to schizophrenia, though similar studies in healthy humans have failed to report replicable or robust effects. Objectives: The present study investigated dexamphetamine effects on PPI in healthy humans with an increased dose and a range of startling stimulus intensities to determine participants' sensitivity and range of responses to the stimuli. Methods: A randomised, placebo-controlled dexamphetamine (0.45 mg/kg, per os.), double-blind, counterbalanced, within-subject design was used. PPI was measured in 64 participants across a range of startling stimulus intensities, during two attention set conditions (ATTEND and IGNORE). Startle magnitudes for pulse-alone and prepulse-pulse magnitudes were modelled using the startle reflex magnitude (sigmoid) function. Parameters were extracted from these fits, including the upper limit of the asymptote (maximum startle reflex capacity, R MAX), intensity threshold, stimulus intensity that elicits a half-maximal response (ES50) and the maximum rate of change of startle response magnitude to an increase in stimulus intensity. Results: Dexamphetamine increased the threshold and ES50 of the response to pulse-alone trials in both sexes and reduced R MAX exclusively in females. Dexamphetamine modestly increased PPI of the R MAX across both attention conditions. PPI of R MAX was reduced during the ATTEND condition compared to the IGNORE condition. Conclusions: Results indicate that sex differences exist in motor, but not sensory, components of the startle reflex. Findings also reveal that administration of 0.45 mg/kg dexamphetamine to healthy humans does not mimic PPI effects observed in schizophrenia.